MO820INTRACELLULAR WATER BEFORE HEMODIALYSIS PREDICTS ALL-CAUSE MORTALITY IN HEMODIALYSIS PATIENTS. (29th May 2021) - Ekart, Robert; Keber, Gasper; Vodošek Hojs, Nina; Jakopin, Eva; Piko, Nejc; Bevc, Sebastjan; Hojs, Radovan
Abstract: Background and Aims: Several factors may be responsible for the increased mortality in dialysis patients, but volume overload is considered among the main mechanisms of this association. Volume status is usually estimated using clinical criteria, i.e., patien's signs and symptoms, peridialytic blood pressure measurements, and intradialytic hemodynamic instability. Bioimpedance analysis (BIA) is another way to measure volume status in dialysis patients. BIA can measure overhydration (OH), extracellular water (ECW), intracellular water (ICW) and ECW/ICW ratio. The aim of our study was to analyze the role of BIA parameters before and after hemodialysis (HD) on all-cause mortality. Method: Eighty-three patients (mean age 64.2 years; 51 men) on maintenance HD were included. BIA was performed and blood pressure was measured before and after the HD session. Patients were followed for assigned time, until transplantation or death. The mean follow-up time was 1181±564 days. Results: Descriptive statistics of our patients are shown in Table 1 . During the follow-up period, 6 (7.2%) patients were transplanted and 39 (47%) patients died. Univariate Cox regression analysis showed that only ICW before HD was a significant predictor of all-cause mortality (HR=1.089; 95%CI: 1.01-1.17, p=0.018). OH, ECW, ECW/ICW ratio before and after HD and ICW after HD were not associated with survival. In multivariate Cox regression analysis including ICW before dialysis, age, dialysis vintage, pulse pressure before HD, hemoglobin, CRP and serum albumin, ICW before dialysis was an independent predictor of all-cause mortality (HR=1.102; 95%CI: 1.01-1.20, p=0.029) (Table 2 ). Conclusion: ICW before HD predicts all-cause mortality in HD patients.